Reexamination of a Battlefield Trauma Golden Hour Policy. Issue 1 (January 2018) - Howard, Jeffrey T.; Kotwal, Russ S.; Santos-Lazada, Alexis R.; Martin, Matthew J.; Stockinger, Zsolt T.
Abstract : BACKGROUND: Most combat casualties who die, do so in the prehospital setting. Efforts directed toward alleviating prehospital combat trauma death, known as killed in action (KIA) mortality, have the greatest opportunity for eliminating preventable death. METHODS: Four thousand five hundred forty-two military casualties injured in Afghanistan from September 11, 2001, to March 31, 2014, were included in this retrospective analysis to evaluate proposed explanations for observed KIA reduction after a mandate by Secretary of Defense Robert M. Gates that transport of injured service members occur within 60 minutes. Using inverse probability weighting to account for selection bias, data were analyzed using multivariable logistic regression and simulation analysis to estimate the effects of (1) gradual improvement, (2) damage control resuscitation, (3) harm from inadequate resources, (4) change in wound pattern, and (5) transport time on KIA mortality. RESULTS: The effect of gradual improvement measured as a time trend was not significant (adjusted odds ratio [AOR], 0.99; 95% confidence interval [CI], 0.94–1.03; p = 0.58). For casualties with military Injury Severity Score of 25 or higher, the odds of KIA mortality were 83% lower for casualties who needed and received prehospital blood transfusion (AOR, 0.17; 95% CI, 0.06–0.51; p = 0.002); 33% lower for casualties receiving initial treatment by forward surgical teams (AOR, 0.67; 95% CI, 0.58–0.78; p < 0.001); 70%, 74%, and 87% lower for casualties with dominant injuries to head (AOR, 0.30; 95% CI, 0.23–0.38; p < 0.001), abdomen (AOR, 0.26, 95% CI, 0.19–0.36; p < 0.001) and extremities (AOR, 0.13; 95% CI, 0.09–0.17; p < 0.001); 35% lower for casualties categorized with blunt injuries (AOR, 0.65; 95% CI, 0.46–0.92; p = 0.01); and 39% lower for casualties transported within one hour (AOR, 0.61; 95% CI, 0.51–0.74; p < 0.001). Results of simulations in which transport times had not changed after the mandate indicate that KIA mortality would have been 1.4% higher than observed, equating to 135 more KIA deaths (95% CI, 105–164). CONCLUSION: Reduction in KIA mortality is associated with early treatment capabilities, blunt mechanism, select body locations of injury, and rapid transport. LEVEL OF EVIDENCE: Therapy, level III.